INNOVATIVE METHODOLOGY IN FINANCIAL ANALYSIS OF INSURANCE ORGANIZATIONS - Elay ZEYNALLI (Akademičnij Oglâd, 2023)
Insurance, which is one of the main avenues of economic diversification, is also important financial and protection mechanism. In order to maintain the activity of insurance organizations and protect them from possible risks, regular financial analysis should be conducted, measures should be taken to make sound financial decisions and protect financial stability. Especially in the new market economy countries, where the “insurance culture” has been not fully formed, financial analysis of insurance organizations can make an important contribution both to strengthening the stability of the country’s financial system and to increasing the confidence of the population in the activities of insurance organizations. In this regard, the theoretical part of the article examines the historical development and modern state of the insurance market in Azerbaijan as a new open market economy country, as well as important state regulations related to financial stability. In the study, the financial analysis of insurance organizations has been conducted on the basis of the specifics of financial analysis in insurance organizations and the recommended financial ratios. The interpretation of the results and the opportunities to improve the financial indicators of the companies have been emphasized.